2015
DOI: 10.5742/mejaa.2015.92694
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Relationship between Vitamin D Status and Basic Functional Mobility in Ambulatory Elderly

Abstract: Background : Associations between physical performance and vitamin D status have been contradicted among studies. Vitamin D deficiency is very common among geriatric patients and is an established risk factor for osteoporosis, falls and fractures. Aim: to analyse the relation between Vitamin D and basic functional mobility in a sample of ambulatory Egyptian elderly. Methods: A cross sectional study was conducted on 100 elderly patients aged ≥ 60 years. Participants were recruited from Geriatric primary health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Most studies on vitamin D deficiency and insufficiency among the elderly in the Middle East have been conducted on women [26,45,46,47,48], a few have included both genders [11,15,49,50], and only one has been conducted solely on men [12]. Low prevalence of vitamin D deficiency has been reported among the elderly in Egypt at 19.3% [12] and KSA at 23.1% [23]; however, insufficiency levels were found to be higher, reaching 41% among the elderly in Lebanon [15] and 77.2% among those in Egypt [26].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on vitamin D deficiency and insufficiency among the elderly in the Middle East have been conducted on women [26,45,46,47,48], a few have included both genders [11,15,49,50], and only one has been conducted solely on men [12]. Low prevalence of vitamin D deficiency has been reported among the elderly in Egypt at 19.3% [12] and KSA at 23.1% [23]; however, insufficiency levels were found to be higher, reaching 41% among the elderly in Lebanon [15] and 77.2% among those in Egypt [26].…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…In a cross-sectional study of vitamin D status in 57 male and 43 female patients aged ≥60 years, Mahmoud et al found that 16% were deficient (serum 25(OH)D ≤ 30 nmol/L) and 52% were insufficient/inadequate (serum 25(OH)D 30–75 nmol/L) [49]. A higher rate of vitamin D deficiency was observed in women than men (20.9% vs. 12.3%, respectively); however, a higher rate of vitamin D insufficiency/inadequacy was observed in than in women men (66.7% vs. 32.6%, respectively).…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%